New phrase in medical lexicon - Abd Razak, Dzulkifli (2004)
HEALTH or medical tourism seems to be a new phrase in medical lexicon. Though it sounds oxymoronic, it is not so, when tourist dollars are associated with it. One Internet source describes medical tourism as the practice of visiting countries with low prices and buying services in their private hospitals or healthcare centers. Another less popular understanding is the case where tourists travel to lessdeveloped countries to offer their medical services at a cost.